2010
DOI: 10.1142/s0129167x10006690
|View full text |Cite
|
Sign up to set email alerts
|

Extremal Almost-Kähler Metrics

Abstract: Abstract. We generalize the notions of the Futaki invariant and extremal vector field of a compact Kähler manifold to the general almost-Kähler case and show the periodicity of the extremal vector field when the symplectic form represents an integral cohomology class modulo torsion. We also give an explicit formula of the hermitian scalar curvature in Darboux coordinates which allows us to obtain examples of non-integrable extremal almost-Kähler metrics saturating LeBrun's estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 20 publications
3
72
0
Order By: Relevance
“…We can then apply Theorem 1.1 to produce compatible extremal metrics Kim and Sung [18] showed that, in any dimension, if one starts with a Kähler metric of constant scalar curvature with no holomorphic vector fields, one can construct infinite dimensional families of almost-Kähler metrics of constant hermitian scalar curvature which concide with the initial metric away from an open set. Similar existence result was presented in [22] when the initial Kähler metric is locally toric.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…We can then apply Theorem 1.1 to produce compatible extremal metrics Kim and Sung [18] showed that, in any dimension, if one starts with a Kähler metric of constant scalar curvature with no holomorphic vector fields, one can construct infinite dimensional families of almost-Kähler metrics of constant hermitian scalar curvature which concide with the initial metric away from an open set. Similar existence result was presented in [22] when the initial Kähler metric is locally toric.…”
Section: Introductionsupporting
confidence: 82%
“…The assumption that T ⊂ Ham(M, ω) is a maximal torus is used only in the second part of Proposition 3.3. Indeed, the arguments in [22] show that z …”
Section: Extremal Almost-kähler Metricsmentioning
confidence: 99%
“…By Tian result [27], there exists a Kähler-Einstein metric except in the first Hirzebruch surface and its blown up at one point (actually these two surfaces are toric). In the latter two cases, the Futaki invariant of the anti-canonical class being non-zero implies that there is no toric HEAK metric [16].…”
Section: Proof Of Theorem 11mentioning
confidence: 99%
“…The Hermitian scalar curvature s is defined as the contraction of ρ ∇ by ω and coincides with the (usual) Riemannian scalar curvature when the metric is Kähler. An almost-Kähler metric is called Hermite-Einstein [16] (HEAK for short) if the Hermitian Ricci form ρ ∇ satisfies ρ ∇ = s ∇ 2n ω (in particular s ∇ is a constant). Note that the terminology 'Hermite-Einstein' here does not imply the integrability of the almost-complex structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation